"Paying the price to get there": Motherhood and the dynamics of pregnancy deliberations among women with disabilities. Issue 3 (July 2017) - LaPierre, Tracey A.; Zimmerman, Mary K.; Hall, Jean P.
Abstract: Background: Women with disabilities report fewer pregnancies than those without disabilities. Objective: To explore the range of factors involved in pregnancy decision-making among women with disabilities, and give insight into the decision making process. Methods: Data were obtained from 4 focus groups conducted with 22 women of child-bearing age, who had a chronic physical or mental health condition or disability that influenced their pregnancy decisions. Group transcripts were analyzed using conventional content analysis to identify the types of factors that influence pregnancy decisions and themes related to pregnancy decision-making. Results: Most had a strong desire for motherhood, although there were varied decisions and some ambivalence over whether or not to attempt pregnancy. Decisions were influenced by an interplay of biomedical, social and personal factors that shaped assessments of three key areas of consideration: importance, feasibility, and costs of pregnancy/motherhood. Conclusions: It is not just the 'biomedical facts' of health conditions that are relevant, but rather the meaning attributed to these facts and how they are weighed in relation to other significant non-medical factors. By moving beyond the medical model of disability to recognize the importance of social and personal factors, and engaging in patient-centered communication, healthcare providers can facilitate pregnancy decision-making that is consistent with the values and preferences of women with disabilities and improve quality of care and support. In order to make motherhood a more viable option for women with disabilities, societal attitudes and a lack of role models for these women also need to be addressed.